Implementasi Keadilan Sosial Perspektif Amos Bagi Gen-Z - Suhartono, Tony; Koptin, Lene (JURNAL IMPARTA, 2024)
Humans are faced with countless kinds of social problems, one of which is the problem of social justice. The practice of social injustice has been going on for centuries, including in the nation of Israel. The Bible clearly writes how the prophet Amos voiced justice and rebuked injustice committed by religious leaders and the Northern Kingdom of Israel. The principle of justice is respect for a person's life. The church as an organizer of social justice has a responsibility to embrace the entire life of the congregation, including generation Z, which currently has the largest population in Indonesia. This research aims to highlight the role of the Church as an organizer of social justice for generation Z. The research method used is a qualitative case study with an example from one of the churches in the Kelapa Gading area, North Jakarta. The research results show that the Church can uphold social justice by developing the lives of generation Z, by teaching God's Word and providing the necessary training through the Training Center. So, through the establishment of the Ensample Training Center, the Church has taken a role in implementing social justice for generation Z.